Cholesterol mass efflux capacity and risk of peripheral artery disease: The Multi-Ethnic Study of Atherosclerosis. (March 2020) - Garg, Parveen K.; Jorgensen, Neal W.; McClelland, Robyn L.; Allison, Matthew; Stein, James H.; Yvan-Chavret, Laurent; Tall, Alan R.; Shea, Steven
Abstract: Background and aims: We aimed to assess the relationship of HDL (high-density lipoprotein)-mediated cholesterol mass efflux capacity (CMEC) with risk of incident peripheral artery disease (PAD). Methods: CMEC was measured in 1458 Multi-Ethnic Study of Atherosclerosis participants between 2000 and 2002 as part of a case-control study matched for incident cardiovascular disease and progression of carotid plaque by ultrasound. Incident clinical PAD, adjudicated on the basis of a positive history for the presence of disease-related symptoms or treatment, was ascertained through 2015 in 1419 individuals without clinical PAD at baseline. Subclinical PAD, defined as an ankle-brachial index (ABI) ≤1.0, was assessed among 1255 individuals with a baseline ABI > 1.0 and at least one follow-up ABI measurement 3–10 years later. Cox proportional hazards and relative risk regression modeling per SD increment of CMEC were used to determine the association of CMEC with clinical and subclinical PAD, respectively. Results: There were 38 clinical PAD and 213 subclinical PAD events that occurred over a mean follow-up of 6.0 and 6.5 years respectively. After adjustment for age, gender, and race, higher CMEC levels were not associated with clinical PAD (hazard ratio 1.25; 95% CI 0.89, 1.75) or subclinical PAD (risk ratio 1.02; 95% CI, 0.94, 1.11). Conclusions: These findings suggest that HDL-mediated cholesterol efflux is not significantly associated with incident clinical and subclinical PAD. Graphical abstract: Image 1 Highlights: Cholesterol mass efflux capacity (CMEC) quantifies the net movement of cholesterol between cells and HDL. We determined the association of CMEC with incident PAD in a multi-ethnic cohort. After adjustment for age, gender, race, higher CMEC levels were not associated with development of PAD. Our findings suggest that CMEC may differentially impact atherosclerotic development across various vascular beds.